Diversity and Habitat Preferences of Odonata in Agricultural Landscapes of Gaya, Bihar, India - Sheha Kumari Bharati; A. Pattanayak; S.N.P Yadav Deen (The Bioscan, 2025)
A comprehensive survey of Odonata species diversity across agricultural landscapes in Gaya revealed 25 species from 4 families, with distinct patterns of abundance and distribution across habitat types. Dragonflies (Anisoptera) were represented by 16 species, with the family Libellulidae being the most diverse, while damselflies (Zygoptera) accounted for 9 species, primarily from the Coenagrionidae family. Diversity indices indicated high species richness in habitats with permanent water, particularly in irrigated croplands (Shannon-Wiener H’ = 3.07), while fallow lands showed the lowest diversity (H’ = 2.1). Odonata species were most abundant in irrigated croplands (51% of species), followed by rainfed croplands (37%) and fallow lands (12%). Seasonal variations also influenced species richness, with peak diversity during the monsoon and lowest richness in winter. Multivariate analysis revealed key environmental factors shaping Odonata diversity, including water availability (r = 0.81, p < 0.01), vegetation cover, and proximity to water bodies. Sensitive species like Ceriagrion coromandelianum and Copera marginipes were associated with undisturbed habitats, while generalists such as Pantala flavescens adapted to both disturbed and undisturbed environments. The study highlights the role of irrigated croplands as biodiversity hotspots and suggests the use of Odonata as ecological indicators in agricultural landscapes, where water availability and habitat structure are crucial determinants of species composition.